Spinal Cord Stimulation (SCS) Trial Outcomes After Conversion to a Multiple Waveform SCS System. Issue 5 (11th June 2018) - Haider, Nameer; Ligham, Dwight; Quave, Brett; Harum, Kirk E.; Garcia, Eduardo A.; Gilmore, Christopher A.; Miller, Nathan; Moore, Gregory A.; Bains, Amarpreet; Lechleiter, Kristen; Jain, Roshini
Abstract : Objective: Spinal cord stimulation (SCS) for chronic intractable pain is typically delivered in pulses, classically programmed between approximately 20 and 100 Hz. Though some recent studies suggest that better pain relief is obtained, with only 10 kHz stimulation, other studies show that single‐therapy trials do not always lead to permanent implantation. We evaluated SCS outcomes in subjects given trials with multiple waveforms who did not experience satisfactory trial relief with 10 kHz stimulation only. Methods: In this multicenter, open‐label, real‐world, observational study conducted in the United States, subjects reporting <50% pain relief with 10 kHz stimulation (i.e., failed the screening trial) received a stimulator capable of delivering multiple waveforms and/or field shapes. Pain relief and patient device preference data were collected. Results: Twenty‐two subjects were analyzed. Of the 16 who failed the 10 kHz trial and had numerical rating scale, visual analog scale, or percent pain relief scores available, 63% ( n = 10) reported ≥50% relief with multiple waveform SCS. Additionally, 80% of subjects with ≥50% relief using multiple waveform SCS had experienced no relief with 10 kHz SCS. Among all subjects, 68% preferred multiple waveform SCS, none preferred 10 kHz SCS, and 32% had no preference. Discussion: Subjects with failed SCS trials at 10 kHz experienced ≥50% relief after switching to a multiple waveform system. These results suggest that providing multiple waveforms during trials may overcome limitations of providing only 10 kHz stimulation. Thus, chronic pain's variable nature across patients and over time lends itself to variable treatment options.